Joint water quantity/quality management analysis in a biofuel production area: Using an integrated economic-hydrologic model - de Moraes, Márcia Maria Guedes Alcoforado; Cai, Ximing; Ringler, Claudia; Albuquerque, Bruno Edson; da Rocha, Sérgio P. Vieira; Amorim, Carlos Alberto (International Food Policy Research Institute, 2009)
Water management in the Pirapama River Basin in northeastern Brazil is affected by both water quantity and water quality constraints. The region is known for significant sugarcane-based ethanol production—which is key to the Brazilian economy and expected to grow dramatically under recent global changes in energy policy. Sugarcane production in the region goes hand in hand with controlled fertirrigation practices with potentially significant adverse impacts on the environment. To assess sustainable water allocation in the basin, an integrated hydrologic-economic basin model is adapted to study both water quantity and water quality aspects. The model results show that incorporating water quality aspects into water allocation decisions leads to a substantial reduction in application of vinasse to sugarcane fields. To enforce water quality restrictions, the shadow price for maintaining water in the reservoir could be used as a pollution tax for fertirrigated areas, which are currently not subject to pollution charges.